SciPost Phys. 2016
DOI: 10.21468/scipostphys.1.1.003
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution during and after finite-time quantum quenches in the transverse-field Ising chain

Abstract: We study the time evolution in the transverse-field Ising chain subject to quantum quenches of finite duration, ie, a continuous change in the transverse magnetic field over a finite time. Specifically, we consider the dynamics of the total energy, oneand two-point correlation functions and Loschmidt echo during and after the quench as well as their stationary behaviour at late times. We investigate how different quench protocols affect the dynamics and identify universal properties of the relaxation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 77 publications
(127 reference statements)
8
77
0
Order By: Relevance
“…[32] and the lines of FZs were indeed found to cross the real time axis at those instants. This observation has been independently confirmed through several works on quenched one-dimensional (1D) integrable and non-integrable systems [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Subsequent studies, however, have established that sudden quenching within the same phase of a system (both integrable and non-integrable) without ever encountering an equilibrium QCP may still give rise to DQPTs in some situations [54,55].…”
Section: Introductionmentioning
confidence: 83%
“…[32] and the lines of FZs were indeed found to cross the real time axis at those instants. This observation has been independently confirmed through several works on quenched one-dimensional (1D) integrable and non-integrable systems [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Subsequent studies, however, have established that sudden quenching within the same phase of a system (both integrable and non-integrable) without ever encountering an equilibrium QCP may still give rise to DQPTs in some situations [54,55].…”
Section: Introductionmentioning
confidence: 83%
“…Further studies, however, revealed that DQPTs can occur following a quench also within the same phase [48][49][50]. Other theoretical works have explored DQPTs in topological and mixed phases [72][73][74][75][76] and also after slow quenches ("ramps") [77][78][79].…”
Section: Dynamical Quantum Phase Transitionsmentioning
confidence: 99%
“…Experimentally, DQPTs have been observed in trapped ions [3,10], cold atoms [11,12], superconducting qubits [13], nanomechanical oscillators [14], and photonic quantum walks [15,16].To date, in most studies of DQPTs, a quantum quench acts as a trigger for initiating nonequilibrium dynamics and then exposing the underlying topological features. However, DQPTs under more general nonequilibrium manipulations are still largely unexplored [17][18][19]. In particular, because the dynamics of systems under time-periodic modulations has led to fascinating discoveries like Floquet topological states [20-24] and discrete time crystals [25][26][27], it is urgent to investigate how DQPTs may occur in such Floquet systems.…”
mentioning
confidence: 99%